Effect of Hollowing Ratio on the Behavior of Hollow Self-Compacting Reinforced Concrete Slender Column Under Eccentric Loading - A. S. Al- Shaarbaf, Ihsan; J. H. Al-zubaidi, Mohammed; A. A. Al- Zaidy, Emad (International Journal of Engineering and Technology, 2018)
In this research the behavior of reinforced concrete slender columns with longitudinal hole under axial compression load and uniaxial bending is investigated. The paper includes testing of ten slender columns with dimensions (150 150 1300 mm). The investigation deals with the effect of using different diameters of  column hole on the values of the load carrying capacity and cracking loads, mid-height lateral deflection and longitudinal shortening of the columns. Five diameters for the column holes were considered (0, 25.4, 38.1, 50.8,  and 76.2)mm. Test results have showed that when the holes were located at the center of the column cross-section and the column was loaded with high load eccentricity, the effect of hollowing ratio on load capacity is insignificant. For hollowing ratios used in this study (0%, 2.3% ,5.1%, 9% and 20.3%), the ultimate load is decreased by (0%, 0.28%, 1.03%, 3.28% and 6.48%) respectively. The effect of hollowing ratio on columns  loaded with small eccentricity of 50mm (e/h=.33)  is greater than the effect of hollow ratio of columns with 150 mm eccentricity(e/h=1.0) which reduces the load capacity  for the columns by (0.00%, 0.66%, 2.65%, 4.97% and 11.26%) for hollowing ratios (0%, 2.3%, 5.1%, 9% and 20.3%) respectively.
Keywords: long column; self-compact concrete; slender column; eccentricity; hole section